Twelve angry men - Rose, Reginald. 4 0 16; 5 (New York : Penguin Books, 2006)
A play in which a juror in a murder trial holds out on a guilty verdict and tries to get the other jurors to look at the situation without being swayed by their personal prejudices or biases.
First published in the United States of America by Dramatic Publishing Co. 1955--T.p. verso.
Adult;Adult
Keywords: 2 -- 0; 6; Legal drama, American.;Legal drama; 20; 2